Rotational Thromboelastometry Derivative Fibrinogen–Platelet Ratio Predicts Thrombosis in Microsurgery - Patel, Harsh; Srinivasa, Dhivya R.; Volod, Oksana; Wang, Eric D.; Kim, Esther A. (Journal of Reconstructive Microsurgery, 2021)
Background Early detection of thrombotic events is of paramount importance for microsurgical procedures. Here, we present findings that underscore the value of rotational thromboelastometry (ROTEM) to aid in decision-making for pre- and postoperative anticoagulation, as well for patients with suspected hypercoagulability.Methods We prospectively collected pre- and postoperative ROTEM values on all free flap cases at the University of California, San Francisco, from 2015 to 2016. Patient age, body mass index, comorbidities, operative reports, risk factors, thrombotic complications, and outcomes were collected from electronic medical records. Two-sample t-tests were used to compare ROTEM values between cohorts. Modeling for sensitivity, specificity, and accuracy was done for threshold fibrinogen-to-platelet ratio (FPR).Results Of 52 patients who underwent free-tissue transfer, 15 had a thrombotic event either intraoperatively or postoperatively that required revision of the vascular anastomosis. Eight patients were clinically hypercoagulable preoperatively, seven of which had a thrombotic event. Several pre- and postoperative ROTEM values differed significantly between thrombotic and nonthrombotic cases. Preoperative (p = 0.027) and postoperative (p = 0.013) FPR were statistically significant when comparing the thrombotic to the nonthrombotic cohort. Threshold FPR ≥ 30 was the most sensitive and FPR ≥ 40 was the most specific.Conclusion Our study affirms other studies that established ROTEM as an effective predictive tool for thrombotic events during free-tissue transfer. However, a lower threshold for FPR improves catchment of thrombotic events and flap failure with acceptable sensitivity. Our results support the routine use of ROTEM for detecting hypercoagulability in patients who would potentially benefit from intervention to prevent thrombotic complications.
Keywords: thromboelastometery; microvascular thrombosis; microsurgery; coagulation; hypercoagulability